The Relationship Between Spirituality/Religiousness and Unhealthy Alcohol Use Among HIV-Infected Adults in Southwestern Ugand - Adong, Julian; Lindan, Christina; Fatch, Robin; Emenyonu, Nneka I.; Muyindike, Winnie R.; Ngabirano, Christine; Winter, Michael R.; Lloyd-Travaglini, Christine; Samet, Jeffrey H.; Cheng, Debbie M.; Hahn, Judith A. (AIDS and Behavior, 2018)
HIV and alcohol use are two serious and coexisting problems in sub-Saharan Africa. We examined the relationship between spirituality and/or religiousness (SR) and unhealthy alcohol use among treatment-naıve HIV-infected adults attending the HIV clinic in Mbarara, Uganda. Unhealthy alcohol was deﬁned as having either an alcohol use disorders identiﬁcation test—consumption score of C4 for men or C3 for women, or having a phosphatidylethanol level of C50 ng/ml based on analysis of dried bloodspot specimens. Of the 447 participants, 67.8% were female; the median age was 32 years (interquartile range [IQR] 27–40). About half reported being Protestant (49.2%), 35.1% Catholic, and 9.2% Muslim. The median SR score was high (103 [IQR 89–107]); 43.3% drank at unhealthy levels. Higher SR scores were associated with lower odds of unhealthy drinking (adjusted odds ratio [aOR]: 0.83 per standard deviation [SD] increase; 95% conﬁdence interval [CI] 0.66–1.03). The ‘‘religious behavior’’ SR subscale was signiﬁcantly associated with unhealthy alcohol use (aOR: 0.72 per SD increase; 95% CI 0.58–0.88). Religious institutions, which facilitate expression of religious behavior, may be helpful in promoting and maintaining lower levels of alcohol use
Keywords: Spirituality/religiousness; Alcohol; HIV; Phosphatidylethanol; Uganda